Crecimiento empresarial de la agencia del Banco Pichincha en la parroquia San Juan en el año 2024. - Jaramillo Álvarez, José Sebastián (2025)
This case study seeks to analyze the elements that contributed to the development and business growth of the Banco Pichincha branch located in the San Juan parish to include the period 2024. It also seeks to evaluate the processes that were used by the entity and how it has had an impact within its locality, marking the key factors that have improved its positioning within the global market. As a data collection method, a survey was used, which was made up of eight questions, which was applied to a sample of 368 people, using as a base a population of 20,768 inhabitants of the San Juan parish of Pueblo Viejo. This tool allowed us to examine different aspects related to the users' perspective on the services offered by the agency, of which we can mention the quality of customer service, the ease of accessing financial products, the efficiency in carrying out banking procedures and the level of trust in the institution. The data obtained shows a high assessment by users of the agency. Among the highlighted elements, we can mention the improvements in the quality of customer service, an increase in service hours and the increase in the diversity of financial products that adapt to needs. Likewise, retention strategies, such as programs dedicated to financial education, discounts and promotions, have strengthened the relationship with users, contributing to the growth of the customer portfolio and a sustained increase in the financial institution's income. The focus on financial incorporation and personalization of services have been determining elements to establish user trust and promote economic reasonableness in the region. The analysis establishes that the institution's business progression is the result of an effective combination of innovation; service planning that adapts to the community and strengthens the relationship with customers.